Palaeomagnetic studies on the dykes of Mumbai region, West coast of deccan volcanic province: implications on age and Span of the deccan Eruptions - Patil, S.K.; Arora, B.R. (2003)
Through detailed AF and thermal demagnetizations of 35 samples (161 specimens) collected from 6 dykes located at Murud region, south of Mumbai, we report the first mean characteristic remanent magnetization direction as D=341°; I= -42°(μ95=5.7; N=6 dykes) for the dykes intruded into the West Coast zone of the Deccan Volcanic Province. The virtual geomagnetic pole (VGP) position (44°N; 83°W; A95=5.8°; N=6 dykes) calculated from this study is compared with those of the Narmada-Tapti zone dykes and with the Deccan Super Pole, proposed by Vandamme et al. (1991). Based on the concordance of these poles and recently reported 40Ar/39Ar and 87Rb/86Sr dates on the dykes of the studied region (Murud), it is proposed that the entire Deccan flows and the associated dykes were erupted in a short interval close to the Cretaceous-Tertiary Boundary at 65.5 Ma. Thermal demagnetization spectra along with isothermal remanent magnetizations and LF test experiments indicated that the SD type titano-magnetite was the major ChRM carrying magnetic mineral in the samples. Out of the 6 studied dykes, one dolerite dyke showing the “reverse magnetic polarity”, could have acted as a feeder dyke to the Poladpur Formation flows, which host the dykes in the studied area. The remaining four dolerite dykes and one lamprophyre dyke, yielding “normal polarity” directions, might have fed to the youngest formations of Wai Subgroup flows, viz., Panhala Formation and Desur Formation, which were eroded in the studied region